Aplicación web para gestionar certificados en formato pdf a partir de una hoja de cálculo y que sean enviados por medio de correos electrónicos: GCEM (2021)
In a fast-paced world in which we live, business processes have required solutions according to the parallel requirements of their mission. This is where the technological tools for processing large data and information are a support for companies to achieve their visionary objectives. The creation of retention certificates is a labor that requires a lot of human effort, where it is done manually from data stored in their records. That is why from a web application you can support and streamline this process, with which the creation and sending of withholding certificate is controlled and later, the data is stored on the server, to allow access to users for management according to specific roles.